MORPHOMETRIC STUDY FOR IDENTIFICATION OF THE BACTROCERA DORSALIS COMPLEX (DIPTERA : TEPHRITIDAE) USING WING IMAGE ANALYSIS - A. ADSAVAKULCHAI'; V. BAIMAI; W. PRACHYABRUED; PAUL J. GROTE; S, LERTLUM (BIOTROPIA, 1999)
The Bactrocera dorsalis complex (Diptera: Tephritidae) used in this study included B. dorsalis, B. arecae, B. propinqua, B. pyrifoliae, B. verbascifoliae, and three new species complexes are species E, species K and species P. Bactrocera tau was used as an out-group. A total of 424 adults, which emerged from pupae collected from natural populations in Thailand, were prepared for wing measurements. Morphometric analysis was performed on measurements of wing vein characters. Wing images were captured in digital format and taken through digitalÂ  image processing to calculate the Euclidean distance between wing vein junctions. Discriminant and cluster analyses were used for dichotomy of classification processes. All 424 wing specimens were classified to species in terms of the percentage of "grouped" cases which yielded about 89.6% accurate identification compared with the formal description of these species. After clustering, the percentage of "grouped"cases yielded 100.0%, 98.9%, 98.1%, 95.2% and 84.6% accurate identification between the B. dorsalis complex and B. tau; B. arecae and Species E; B. dorsalis and B. verbascifoliae; B. propinqua and B. pyrifoliae; and species K and species P, respectively. This method of numerical taxonomy may be useful for practical identification of other groups of agricultural pests. Key words: Bactrocera dorsalis complex/wing image processing/morphometric/discriminant and cluster analyses.